Enhancing The CBTC System in Urban Rail Transit - Ngadiron, Zuraidah; Bachok, Syariah; Kamaluddin, N.A. (2022)
In recent years, urban rail transit has developed rapidly around the world due to its safety, reliability, high capacity and energy efficiency. Furthermore, it is faster, safer, more comfortable and it has high capacity, which significantly related to communication based train control system (CBTC). That’s how the demand for urban rail transit is increasing faster and lots of urban rail transit projects are constructed in especially big cities in order to reduce traffic and improve public transport quality. However, the majority of CBTC systems rely on Wireless Local Networks (WLAN) technology, which cannot fully provide data transfer during train operation at high-speed. Therefore, in urban rail transit, Long Term Evolution (LTE) has become a burden on the research communication technology due to a high transmission speed. Yet, there is a few study on the dependability of LTE based train ground communication systems. This study, will focus on the dependability of train ground communication, train ground communication performance parameters of based on LTE technology, the dependability analysis according to the experimental results, behaviour comparison, storage process and data observation of train data in operation in order to analyse the dependability of train data transmission. Its seems that the consistency of LTE-based train ground communication is important and fulfils CBTC requirements.